Studi Parameter Fisika Kimia Air pada Areal Budidaya Ikan di Danau Tondano, Desa Paleloan, Kabupaten Minahasa - Tatangindatu, Frits; Kalesaran, Ockstan; Rompas, Robert (e-Journal BUDIDAYA PERAIRAN, 2013)
The purpose of this research was to analyze the physical and chemical parameters of waters (temperature, turbidity, pH, dissolved oxygen, nitrate, phosphate, ammonia and BOD) around net cage culture area at Peleloan Village, Minahasa Regency and to determine the suitable culture site supporting optimal growth of fish. water quality was measured at three sites. Temperature, turbidity, and pH were measured in situ while dissolved oxygen, nitrate, phosphate, ammonia and BOD were analised in laboratorium. Research results showed water temperature at all observation sites ranged from 25.5-28.2 0C, turbidity 2.02-3.15 m, pH 6.8 – 8.2, DO 7.41-7.77 mg/L, nitrate 0.3-0.5 mg/L, phosphate 0.00-0.4 mg/L, ammonia 0.13-0.77 mg/L. Based on water quality standard criteria stated in PP No. 82, 2001, temperature, turbidity, pH, DO and nitrate at fish culture area were suitable for floating and stick net cage cultures but ammonia at all sites of observation, phosphate at site I at 0.5 m from the bottom and BOD at site III at 0.5 m from the bottom were exceeding the standard criteria. Keywords: water physical and chemical Parameters, floating net cage, Lake Tondano, Paleloan Village